2018
DOI: 10.1109/jssc.2018.2870555
|View full text |Cite
|
Sign up to set email alerts
|

Sub-<inline-formula> <tex-math notation="LaTeX">$\mu$ </tex-math> </inline-formula>Vrms-Noise Sub-<inline-formula> <tex-math notation="LaTeX">$\mu$ </tex-math> </inline-formula>W/Channel ADC-Direct Neural Recording With 200-mV/ms Transient Recovery Through Predictive Digital Autoranging

Abstract: Integrated recording of neural electrical potentials from the brain poses great challenges due to stringent dynamic range requirements to resolve small-signal amplitudes buried in noise amidst large artifact and stimulation transients, as well as stringent power and volume constraints to enable minimally invasive untethered operation. Here, we present a 16-channel neural recording system-on-chip with greater than 90-dB input dynamic range and less than 1-µV rms input-referred noise from dc to 500 Hz, at 0.8-µW… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 80 publications
(19 citation statements)
references
References 20 publications
0
19
0
Order By: Relevance
“…This structure is called 2 ADC . (C) An auto-ranging quantizer in 2 makes it possible to follow sudden changes in the input signal (Kim et al, 2018).…”
Section: Adc-direct Front-endmentioning
confidence: 99%
See 2 more Smart Citations
“…This structure is called 2 ADC . (C) An auto-ranging quantizer in 2 makes it possible to follow sudden changes in the input signal (Kim et al, 2018).…”
Section: Adc-direct Front-endmentioning
confidence: 99%
“…signal to the integrator in main path by around 30 dB Bang et al, 2018;Kim et al, 2018;Reza Pazhouhandeh et al, 2020). Furthermore, the integrator in the main path can be implemented by a low-power open-loop Gm-C filter owing to its small input, allowing for drastic power reduction.…”
Section: Adc-direct Front-endmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, portable wearable bio-electricity signal monitoring devices are playing an significant part in the field of modern medicine [1,2]. A bio-electricity signal acquisition system usually consists of an analog front-end amplifier and an analog-to-digital converter (ADC).…”
Section: Introductionmentioning
confidence: 99%
“…In particular, an AC-coupled closed-loop amplifier that is one of the most widely used neural recording amplifiers must have a high-performance OTA inside because it mainly determines the overall performance necessary for neural recordings, such as low input-referred noise (IRN), large bandwidth, low power, and small area consumptions, acceptable input/output signal ranges, and low distortion. Recent state-of-the-art neural recording amplifiers have been extensively explored by adopting various OTA topologies, such as a current mirror [8], two-stage [4,5,[16][17][18], and folded cascode (FC) OTAs [9,[19][20][21], in addition to the novel circuit design techniques [13,[20][21][22][23]. Among the aforementioned OTA topologies, the FC-OTA has demonstrated that it reached the theoretical noise efficiency factor (NEF) limit of roughly 2 (~2.67), without adding the special circuit design techniques such as pre-amplification, current-reuse, and body biasing, and with the simple adaptation of large current scaling ratio and source degeneration [9].…”
Section: Introductionmentioning
confidence: 99%